Interventional and Non-interventional Medical Rehabilitation Approaches to Axial Spine Pain in Vertebral Metastatic Disease - Sarma, Krishna; Kohns, David J.; Berri, Maryam A.; Joyce, Elizabeth; Smith, Sean R. (Frontiers in Pain Research, 2021)
As targeted therapies help patients with advanced cancer live longer, interventions for management of axial spine pain will become more common. Unfortunately, the indications for and safety of these procedures have been relatively unexplored compared to non-cancer adults. This review focuses on the following aspects of axial spine pain management in patients with vertebral metastatic disease: 1) pathophysiology and symptoms of cancer- and non-cancer related spine pain; 2) safety and efficacy of non-interventional rehabilitation approaches to treat this pain; 3) considerations for interventional pain approaches to acute and chronic pain in patients with vertebral metastatic disease. This review also summarizes gaps in the literature and describes specific cases in which the described interventions have been applied.